How to keep well in wartime - Great Britain. Ministry of Health ; Central Council for Health Education (Great Britain); Clegg, Hugh Anthony, 1900- (London : His Majesty's Stationery Office, 1943)
1943 1943 1940s 28 pages : illustrations STOP GERMS FROM SPREADING 1,000 bombers, and 1,000,000 rifles in one year. It may not be possible to get rid of all "droplet" infections; they are more difficult to control than the infections — such as typhoid fever and cholera — that used to come from a dirty water supply. Don't Pass Your Cold On. One way to stop germs spreading from one person's throat to another's is to isolate the infected person. If everyone at the very first sign of a cold were to go promptly to bed and stay there for one or two days, then the common cold would not be so common as it is, and everyone would lose much less time at work. The usual thing that happens is that a girl goes to her office with a streaming cold, gives it to most people with whom she comes in contact (in bus or tube or tram, as well), and on the second day sends a message to say she is worse and cannot come. By this time, of course, she has infected a large number of people, and has made her own cold worse by going to work. And she will end up by losing more time from work than if she had gone to bed straight away. There is an obvious way of stopping germs getting from your month and throat into the air around you — and that is to cover your mouth and nose with a handkerchief every time you cough or sneeze. To cough or sneeze without doing this is a rude and disgusting habit, and it is amazing how many people, through thoughtlessness, have this habit. A sneeze may, of course, take you very suddenly, and you have to cover your mouth and nose with your hand. There is a peculiar thing about germs, and that is that dangerous germs may lodge in your throat without doing you any harm. But they may prove harmful to other people. Those who have dangerous germs about their body without being ill are called "carriers". So, you see, it is important to cough and sneeze into your handkerchief and into the air, whether you have a cold or not. Inoculation May Save Your Child's Life. Another way of preventing infection is by inoculating or vaccinating people against certain germs. In the last war (and in the present one) our soldiers were inoculated against typhoid fever, and they consequently suffered much less from this than they did in the South African War. Many of the civilian population have been inoculated against typhoid in the past two years because the risk of contamination of the water supply is greater during wartime. Fortunately typhoid fever has not shown any increase. Diphtheria is another disease doctors are trying to stamp out by inoculation. There are about 60,000 cases of diphtheria, mostly in children under ten, in Great Britain every year. Out of this number about 3,000 deaths occur — mostly of children under five. Inoculation against diphtheria — diphtheria immunization, as it is called — is absolutely safe and practically painless. It means little more than the prick of a needle on two occasions. Diphtheria could be stamped out if all the children in the country, or even four out of five of them, 21 420/BS/7/16/18